THE FACTORS THAT INFLUENCE THE PARTICIPATION OF NON-ENGLISH MAJOR STUDENTS IN ENGLISH CLASSROOM ACTIVITIES - Helena Tada; Chairil Anwar Korompot; Geminastiti Sakkir (International Journal of Business English and Communication, 2025)
This study aims to identify the factors that influence non-English major students' participation in English classroom activities. A qualitative approach was used, with data collected through in-depth interviews. Three students participated in the interviews. The results indicate that the main factors influencing participation include students' interest in the learning topic, teaching style of the lecturer, self-motivation, and the teaching method. In conclusion, this research highlights the significant role of the discussion-based method and student interest in promoting active participation.